Taxonomic review of the Genus Deltoplastis Meyrick (Lepidoptera: Lecithoceridae) in China and its neibouring countries, with a world catalogue of the genus - Wang, Yuqi; Park, Kyu-Tek; Wang, Shuxia (Zootaxa, 2015)
The genus Deltoplastis Meyrick is reviewed from China and its neibouring countries. Fifteen species are recognized, including nine new species: D. angustifoliacea sp. nov., D. conjugata sp. nov., D. dentata sp. nov., D. curviloba sp. nov., D. gyroflexa sp. nov., D. hippocrepica sp. nov., D. mamillata sp. nov., D. acutiprocessa sp. nov., and D. maehongsonensis sp. nov. The male of D. causidica (Meyrick, 1910) and the female of D. prionaspis Gozmány, 1978 are described for the first time. Deltoplastis causidica (Meyrick, 1910) from China and Thailand, D. gypsopeda Meyrick, 1934 from Thailand and India, D. commatopa Meyrick, 1932 from Vietnam and India, D. lobigera Gozmány from India are newly recorded for each country. Photographs of adults and genitalia are provided, along with a key to the species and a world catalogue of Deltoplastis.